2021
DOI: 10.3389/fcimb.2021.656674
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiome Characteristics in Patients With Autoimmune Hepatitis

Abstract: Autoimmune hepatitis (AIH) is a common cause of liver cirrhosis. To identify the characteristics of the oral microbiome in patients with AIH, we collected 204 saliva samples including 68 AIH patients and 136 healthy controls and performed microbial MiSeq sequencing after screening. All samples were randomly divided into discovery cohorts (46 AIH and 92 HCs) and validation cohorts (22 AIH and 44 HCs). Moreover, we collected samples of 12 AIH patients from Hangzhou for cross-regional validation. We described the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Dysbiosis has been found in the oral and gut microbiome of patients with chronic hepatitis B [ 52 ], liver cirrhosis [ 53 ], primary sclerosing cholangitis [ 54 ] and hepatocellular carcinoma (HCC) [ 55 ]. A recent epidemiological study reported a significantly increased diversity also in AIHp oral microbiome [ 27 ], with seven genera, mainly Fusobacterium, Actinomyces and Capnocytophaga, decreased in saliva of AIHp with respect to controls, and 51 genera, mainly represented by Streptococcus, Veillonella and Leptotrichia, increased. These findings suggest that elevated level of histatins in saliva of AIHp may represent a physiological protective mechanism against pathogens in the oral cavity to counter these persistent infections and inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysbiosis has been found in the oral and gut microbiome of patients with chronic hepatitis B [ 52 ], liver cirrhosis [ 53 ], primary sclerosing cholangitis [ 54 ] and hepatocellular carcinoma (HCC) [ 55 ]. A recent epidemiological study reported a significantly increased diversity also in AIHp oral microbiome [ 27 ], with seven genera, mainly Fusobacterium, Actinomyces and Capnocytophaga, decreased in saliva of AIHp with respect to controls, and 51 genera, mainly represented by Streptococcus, Veillonella and Leptotrichia, increased. These findings suggest that elevated level of histatins in saliva of AIHp may represent a physiological protective mechanism against pathogens in the oral cavity to counter these persistent infections and inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, while the possible use of saliva as a diagnostic fluid has been largely investigated for oral and systemic diseases [ 25 , 26 ], it has been only marginally used in autoimmune liver diseases, mainly to investigate the role played by oral microbiota in their pathogenesis [ 27 ]. As a mirror of oral and systemic health, saliva provides valuable information because it contains not only proteins specifically secreted by the salivary glands [ 28 ], but also proteins from the gingival crevicular fluid [ 29 , 30 ], from oral microflora [ 31 ] and plasmatic proteins transported from blood to saliva by both intra- and extracellular pathways.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a considerable number of studies about the application of gut microbiota as diagnostic biomarkers for liver diseases such as liver cirrhosis, autoimmune hepatitis and hepatocellular carcinoma (HCC) have been published ( Qin et al., 2014 ; Ren et al., 2019 ; Rao et al., 2021 ) but have not addressed SBP. The present research evaluated the altered gut microbiota in SBP patients and the possible relationship between the gut microbiota and disease progression, and explored a specific gut microbiota profile as a biomarker panel and redound to establish a noninvasive diagnostic model in screening for SBP at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…Bar plots of the gut microbial community were generated to exhibit bacterial taxonomic analysis at the phylum, class, order, family, and genus levels. Alpha diversity was assessed by the Shannon index, and principal coordinate analysis was used to determine beta diversity among samples [ 33 ]. The Spearman correlation analysis was performed to determine the relationship between the human-derived proteins and calprotectin.…”
Section: Methodsmentioning
confidence: 99%